Le jardinage dans l’espace public : paradoxes, ruses et perspectives - Aurélien Ramos (Projets de Paysage)
Among the public policies in support of nature in urban areas developed since 2007 in the wake of the Grenelle de l’environnement (Environmental Round Table), the measures encouraging city dwellers to garden in public spaces constitute an innovative form of governance. These policies institutionalise gardening as a "tactic" and consist of the exceptional authorisation of amateur gardening in public spaces. The condition for such an authorisation lies in the calibration of these gardening initiatives and, paradoxically, in their informal nature. This incentive for the urban dweller introduces the individual as an element impacting the transformation of the city and raises questions concerning the role of designers. This article uses data from a database of eighteen French cities where such initiatives have been in existence since 2004. It aims to define the general outlines of these incentive-based policies to analyse the challenges faced and to conduct an initial review.